2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649253
|View full text |Cite
|
Sign up to set email alerts
|

Isothermic vs thermoneutral hemodiafiltration evaluation by indirect calorimetry

Abstract: HD and HDF as hemodialytic therapies normally alter patient's haemodynamic stability, due to the inflammatory response to extracorporeal blood circuit, producing increment of the core temperature (+1.0 degrees C). However, such increase in temperature could be controlled by lowering dialysate's temperature using two main modalities techniques (isothermic and thermoneural) with different patient's thermal balance consequences, not yet well studied. In this work, energy expenditure (EE) was measured by indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Evaluating REE in hemodialysis with dialysate at different temperatures, Hor acek et al [34] found no change in REE of patients with CKD. On the other hand, Cadena et al [35] and Rokyta et al [36] observed changes in REE during dialysis treatment in AKI patients. Cadena et al [35] observed a REE increase when used dialysate adjusted to maintain body temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluating REE in hemodialysis with dialysate at different temperatures, Hor acek et al [34] found no change in REE of patients with CKD. On the other hand, Cadena et al [35] and Rokyta et al [36] observed changes in REE during dialysis treatment in AKI patients. Cadena et al [35] observed a REE increase when used dialysate adjusted to maintain body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Cadena et al [35] and Rokyta et al [36] observed changes in REE during dialysis treatment in AKI patients. Cadena et al [35] observed a REE increase when used dialysate adjusted to maintain body temperature. Rokyta et al [36] observed decrease in REE during dialysis procedure with "cold" replacement fluid (maintained at 20 C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RRT may also lead to a reduction in body temperature and decrease REE. 25 Thus, the comparison between these two studies may be impaired.…”
Section: Discussionmentioning
confidence: 99%